Higher Education, Military Affairs, and Ethics: A Historical Overview of a Progressive Civil Rights Movement (Global Journal of Human-Social Science, 2017)
Leaders within the higher education community are uniquely suited to promote progressive social changes within the United States of America. This essay examines the efforts of higher education professionals to promote gay rights within American society. Efforts college campuses and the subsequent litigation were strategies used to promote equality within the military, college campuses, and society. This essay examines the historical steps taken to achieve progressive social change.
Keywords: military; higher education; civil rights; recruiting; law